Meta Analysis of the Influence of Entrepreneurship Education on Students' Entrepreneurial Interest - Tamba, Jubaria; Naibaho , David Tamado; Ingtyas , Fatma Tresno; Ginting, Laurena (CV. Tripe Konsultan, 2024)
This study is a meta-analysis aimed at examining the influence of entrepreneurship education on university students' entrepreneurial intentions. Data were derived from 15 articles published in academic journals between 2019 and 2024, using a descriptive qualitative approach. The findings reveal that entrepreneurship education significantly enhances entrepreneurial intentions by developing entrepreneurial skills, mindsets, and attitudes. Internal factors, such as personal motivation and self-confidence, as well as external factors, such as family support and campus environment, also influence entrepreneurial intentions. Additionally, practice-based learning methods are proven to be more effective than theoretical approaches in fostering entrepreneurial intentions among students. While most studies indicate positive effects, the effectiveness of entrepreneurship education can be influenced by the approaches applied and external support. This study recommends a holistic approach to maximize the impact of entrepreneurship education on students' entrepreneurial intentions.